2018
DOI: 10.1080/24734306.2018.1549804
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of snakebite in dogs in Sri Lanka

Abstract: Dogs (Canis familiaris) have several behavioral characteristics that may contribute to snakebites. Dogs generally are inquisitive, lack ophidiophobia (fear of snakes), and may attack a snake in defense of self or a human companion. This is a descriptive cross-sectional study of 115 dogs presented to the Veterinary Teaching Hospital during a 36 month period with bites caused by three venomous snakes namely; Russell's viper, (Daboia russelii: n ¼ 65) cobra (Naja naja: n ¼ 36) and hump nosed viper (Genus Hypnale:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Consistent with studies of snakebite incidence from other venomous snakes this study observed a higher proportion of males suffered HNPV bites. It is hypothesised this reflects the more prominent territorial behaviour of male dogs 8 , 22 , 23 . This observation parallels the incidence of snakebite in human males in farming communities due to social norms governing occupational roles 4 , 25 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Consistent with studies of snakebite incidence from other venomous snakes this study observed a higher proportion of males suffered HNPV bites. It is hypothesised this reflects the more prominent territorial behaviour of male dogs 8 , 22 , 23 . This observation parallels the incidence of snakebite in human males in farming communities due to social norms governing occupational roles 4 , 25 .…”
Section: Discussionmentioning
confidence: 96%
“…H. hypnale is most commonly found under stones, logs and leaf litter in and around human settlements. Therefore, the pattern of behaviour of both dog and HNPV increases the possibility of envenoming in dogs at dusk and dawn 8 . By contrast the majority of HNPV bites in human are reported in day time in their home gardens 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictable local and systemic effects due to envenoming and their progression were documented according to studies conducted by Refs. [2,19,3], on envenoming. Expected local clinical manifestations of envenoming due to Russell’s viper bites included inflammation (swelling, pyrexia, and erythema), bruising, blistering, and local necrosis at the site detected by fang marks, pain, haemorrhages from inter-digital spaces and gingival regions, lymphadenopathy, and infected wounds at the site of the bite.…”
Section: Methodsmentioning
confidence: 99%
“…It is the deadliest venomous viper in Sri Lanka [1,2]. The high morbidity and mortality due to snakebites in dogs in Sri Lanka result from Russell's viper ( Daboia russelii ), cobra ( Naja naja ), and hump nosed viper (Genus Hypnale ) [3]. The proteome profile of Sri Lankan Russell’s vipers is identical, where composition of the venom is dominated by the neurotoxic basic phospholipases A2 (>30% of total protein abundance) and several hemotoxic or coagulopathic protein families (approximately 50% in total) and is correlated with the functional and toxinological characterizations of the venom, and reflects the pathophysiological effects of envenoming [4].…”
Section: Introductionmentioning
confidence: 99%